Aristophanes on Solon and His Laws - Leão, Delfim (2022)
In Aristophanes work, the references to the laws of Solon are relatively scarce: there are two allusions in Birds (Av. 1353-57; 1660-64), one in Clouds (Nub. 1178-95), and a fragment from the lost comedy Banqueters (Dait. fr. 233 Kassel and Austin). An equal number can be found in four scholia to passages: again from Birds (Av. 1354; 1541) and Clouds (Nub. 37), and another from Knights (Eq. 658). Despite this relative paucity, those occurrences prove that Aristophanes was familiar with Solon’s laws, which he uses mainly for parodic purposes. The aim of this paper is to analyse those passages in their proper context and in comparison with passages from other authors, in order to discuss their validity as sources for the study of Solon’s laws.